The big bad world of concept art for video games vol. 2 how to start your career as a concept artist - Lilly, Eliott (Los Angeles, CA Design Studio Press, 2017)
"The big bad world of concept art for video games: how tp start your career as a concept artist is book two in the big bad series, delving deeper into the subjects and topics explored previously in An Insider's Guide for Students. Going beyond the amateur level, this guide prepares the upcoming professional, or any other artist, for a future in the entertainment industry. Whether you are a graduating student joining the workforce, a young professional who has just broken into the job market, or even an existing professional frustrated with your current situation, receive help figuring out what comes next for a fulfilling career." -- Provided by publisher
Keywords: Conceptual art; Computer artists -- Vocational guidance; Video games -- Design -- Vocational guidance